On the Agenda? Deliberations on Experiential Learning at Canadian University Senate Meetings, 2012-2022 - Buzzelli, Michael; Narh, Ebenezer (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2025)
The university’s core teaching mission is being reshaped by the proliferation of experiential learning (EL) pedagogies. The rise of EL is also constituting new connections between the university and its local community, relationships necessary for EL itself to be delivered. This research examines how universities confront these new and mutually interdependent dimensions of teaching and societal engagement. Using qualitative thematic content analysis, the paper documents and analyses university senate deliberations on EL at twelve (12) representative institutions in Canada for the period from 2012 to 2022 (n = 922 monthly meetings). Focusing on senate discussions on matters such as internal university EL governance, engagement with community partners, and impacts on learners and learning, the paper presents a novel analysis of the Canadian university’s understanding and development of EL in this phase of expansion. The paper concludes with a discussion of institutional and sector policy implications for the teaching and learning mission.